THE SYMBOLIC STATUS OF THE "PIG" ZOONYM IN VIETNAMESE AND UZBEK CULTURES: A LINGUOCULTURAL ANALYSIS - Muydinova , Gulnigorkhan (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article examines the symbolic status of the zoonym "pig" in Uzbek and Vietnamese cultures from a linguocultural perspective. The study demonstrates the influence of religious, historical, and economic factors on phraseological semantics; it compares the negative connotations shaped by Islam in Uzbek culture with the bipolar (positive and negative) symbolism linked to the 12-year animal calendar and rural economy in Vietnamese culture.